Guessing Game: an Implementation in Speaking Class of High School Students - Rustam, Utary; Amir, Hasbiyah Sriana (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2022)
One of fun game to teach English is through guessing game. It can develop concept, add diversion to regular activities or just to break the ice. It will make students become more excited in studying English in the classroom, especially speaking skill. The purpose of this reasearch is to find out whether the use of guessing game is able to improve speaking ability of the tenth year students in MA Al-Munawwarah Parepare. This research applied a Classroom Action Research with two cycles. The result of the mean score in cycle 1 and cycle 2 showed that students’ speaking ability improved significantly. It is shown from the mean score in cycle 1 (58,47) increase in cycle 2 (77,5). Besides, the result of observation showed students’ participation increase in the classroom. It can be concluded that the use of guessing game is able to improve students’ speaking ability and students’ activeness in the learning process.